WRITTEN ASSIGNMENTS IN TECHNOLOGY ENHANCED POST GRADUATE COURSES IN TESOL - VLACHOS, KOSMAS (Online Learning, 2025)
The research paper explores the impact of assignments on enhancing educational technology awareness among postgraduate trainee English language teachers at the Hellenic Open University. The study focused on participants in the teaching of English as a foreign language (EFL) program, specifically those engaging in the 13-week training module (Agg31) on the use of modern technologies in English teaching. The training involved distance learning materials, three four-hour sessions, forum discussions, and the completion of two substantial written assignments presented in a plenary format known as VIVA. During the academic year 2022–2023, 50 trainee teachers, split between winter and spring semesters, participated in the study. The research utilized closed- and open-ended questions, with 10 trainees engaging in focus group discussions to elaborate on questionnaire responses. Descriptive statistics and content analysis were employed for data examination. Results indicated that the guidance received during sessions and the collaborative network significantly contributed to the creation of successful assignments with educational scenarios. These assignments, often implemented in classrooms, expanded trainees’ understanding of new media methods. The VIVA sessions provided opportunities for reflection and expressing a commitment to continuous learning. Trainees felt supported and inspired, fostering a desire to explore and exchange ideas for innovative techniques and resources. Overall, the study concluded that assignments played a pivotal role in elevating educational technology awareness among postgraduate trainee teachers, fostering a positive and collaborative learning environment.